Design of e-government mobile application for certificate issues in Sukapura village - Islam, Mushlih Nur; Syazwani, Savira Denisa; Wibowo, Muhammad Rizky; Dirgantoro, Burhanuddin; resptiawan, reza rendian; ahmad, umar ali (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2025)
This study presents the Capstone Project, which seeks to digitize public services in Sukapura Village through a mobile application to address current conventional service challenges. The project introduces a village service digitization system integrated with the OpenSID system. The system offers accessibility for both the community and village officials. The project's aims include problem identification, effective solution provision, and implementation of digitized public services via mobile apps. Test 4 involves two distinct methods: alpha and beta testing. Alpha testing employs automation tests to examine mailing services, while beta testing uses Google forms for user acceptance tests. The alpha testing analyzes the flow of letter submissions encompassing various types. Pre-established objectives guide testing, considering 0.7 as the minimum reliability coefficient. Analysis of both testing methods indicates promising results in terms of user interface and experience, as sufficient data was gathered from the conducted tests.